Experimental Study of a Novel PV/T- Air Composite Heat Pump Hot Water System. (May 2015) - Wang, Gang; Quan, Zhenhua; Zhao, Yaohua; Xu, Peng; Sun, Chenming
Abstract: Solar energy utilization and heat pump are common technologies of renewable energy utilization for solving the problem of energy crisis and environmental pollution in present. This paper proposed a novel PV/T-air composite heat pump hot water system. The system was comprised of independently developed flat plate solar PV/T collector based on micro-channel heat pipe array and air source heat pump, which were combined by a new composite evaporator. The performance of the system were experimentally studied, COP of heat pump reduced from 5.61 to 1.69 and the average was 3.03. Comprehensive COPsys of PV/T-air composite heat pump system ranged from 6.07 to 1.33, the average was 2.99. The result showed the system was worthy of promotion and application.